Kidney-Induced Hypertension Depends on Superoxide Signaling in the Rostral Ventrolateral Medulla - Oliveira-Sales, Elizabeth B.; Colombari, Debora S. A. [UNESP]; Davisson, Robin L.; Kasparov, Sergey; Hirata, Aparecida E.; Campos, Ruy R.; Paton, Julian F. R. (Lippincott Williams & Wilkins, 2010)
Reactive oxygen species in peripheral cardiovascular tissues are implicated in the pathogenesis of 2 kidney-1 clip hypertension. We recently identified an imbalance between reactive oxygen species generation and oxidant scavenging in the rostral ventrolateral medulla (RVLM) of 2 kidney-1 clip in rats. We tested whether enhanced superoxide signaling in RVLM of 2 kidney-1 clip rats contributes to the chronic hypertension via sympathetic activation in conscious rats. We enhanced superoxide scavenging in RVLM by overexpressing cytoplasmically targeted superoxide dismutase using an adenoviral vector (Ad-CMV-CuZnSOD) in Wistar rats (male, 150 to 180 g) in which the left renal artery was occluded partially 3 weeks earlier. Hypertension was documented using radiotelemetry recording of arterial pressure in conscious rats for 6 weeks. Renovascular hypertension elevated both serine phosphorylation of p47phox subunit of NADPH and superoxide levels in RVLM. The elevated superoxide levels were normalized by expression of CuZnSOD in RVLM. Moreover, the hypertension produced in the 2 kidney-1 clip rats was reversed 1 week after viral-mediated expression of CuZnSOD. This antihypertensive effect was maintained and associated with a decrease in the low-frequency spectra of systolic blood pressure variability, suggesting reduced sympathetic vasomotor tone. The expression of CuZnSOD was localized to RVLM neurons, of which some contained tyrosine hydroxylase. None of the above variables changed in control rats receiving Ad-CMV-eGFP in RVLM. In Goldblatt hypertension, superoxide signaling in the RVLM plays a major role in the generation of sympathetic vasomotor tone and the chronic sustained hypertension in this animal model. (Hypertension. 2010;56:290-296.)
Keywords: hypertension; renal; blood pressure; heart rate; brain; free radicals